2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31298
|View full text |Cite
|
Sign up to set email alerts
|

Work in Progress: Online Training in Spatial Reasoning for First-year Female Engineering Students

Abstract: Birkhimer conducts research and leads retention activities including administration of the undergraduate and graduate mentoring programs and the teaching of the Women in Engineering seminar courses. For the past decade, Dr. Zurn-Birkhimer's research has focused on broadening participation of women and underrepresented group in STEM fields. Recently, she has been investigating the intersection of education and career path with cultural identity and is developing strategies to inform programming and policies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Both the experimental group and the control group saw a statistically significant increase in their spatial ability as determined by the Purdue Spatial Visualization Tests (PSVT). No statistically significant difference was seen in the gains of the experimental group versus gains in the control group however, the experimental group achieved passing test scores of 70% or greater on each of the three PSVTs by the post-test whereas the control group failed to reach this level 16 .…”
Section: Introduction and Related Workmentioning
confidence: 66%
See 1 more Smart Citation
“…Both the experimental group and the control group saw a statistically significant increase in their spatial ability as determined by the Purdue Spatial Visualization Tests (PSVT). No statistically significant difference was seen in the gains of the experimental group versus gains in the control group however, the experimental group achieved passing test scores of 70% or greater on each of the three PSVTs by the post-test whereas the control group failed to reach this level 16 .…”
Section: Introduction and Related Workmentioning
confidence: 66%
“…Hsi et al 15 also found that a one-day workshop on 2D and 3D sketching led to an enhancement in spatial strategies to solve engineering problems. A pilot study was conducted by Zurn-Birkhimer et al 16 for the development and implementation of a semester-long, 12-module workshop consisting of four origami-based modules followed by eight CAD-based modules 16 . Both the experimental group and the control group saw a statistically significant increase in their spatial ability as determined by the Purdue Spatial Visualization Tests (PSVT).…”
Section: Introduction and Related Workmentioning
confidence: 99%